SATB1 in cancer progression and metastasis: mechanisms and therapeutic potential - Bai, Jinping; Yang, Gege; Yu, Qi; Chi, Qianya; Zeng, Xianlu; Qi, Wenjing (Frontiers in Oncology, 2025)
Cancer remains a major global health challenge, with prostate cancer, lung cancer, colorectal cancer, and breast cancer accounting for nearly half of all diagnoses. Despite advancements in cancer treatment, metastasis to distant organs continues to be the leading cause of cancer-related mortality. The progression of cancer involves the alteration of numerous genes, with dynamic changes in chromatin organization and histone modifications playing a critical role in regulating cancer-associated genes. Special AT-rich sequence-binding protein 1 (SATB1), a critical chromatin organizer, plays a pivotal role in cancer progression by regulating gene expression, chromatin remodeling, and cell signaling pathways. SATB1 binds to AT-rich DNA sequences, acting as a scaffold for chromatin-modifying enzymes and transcription factors, thus coordinating the regulation of extensive gene networks. Its overexpression has been implicated in a wide range of cancers and is associated with poor prognosis, aggressive tumor phenotypes, and enhanced epithelial–mesenchymal transition (EMT). Moreover, SATB1’s activity is modulated by microRNAs (miRNAs) and post-translational modifications, further contributing to its complex regulatory functions. Given its crucial involvement in cancer progression and metastasis, SATB1 has emerged as a promising target for novel therapeutic strategies. This review delves into the molecular mechanisms of SATB1 in cancer and explores potential therapeutic approaches for targeting this key regulator in cancer treatment.